Effect of Separation Medium, Addition of Coffee Extract Before Sexing X and Y Sperm Chromosome and Storage Period on Quality of Fresh Semen of Ettawa Cross Goat - . Hasbi; H. Sonjaya; S. Gustina (Jurnal Ilmu dan Teknologi Peternakan, 2011)
One problem in the application of biotechnology in spermatozoa sexing of X and Y sperm chromosome is a decrease in motility and percentage of live spermatozoa. The decrease could be caused by metabolic process, therefore spare energy obtained from separation medium is decreasing resulting in decrease in motility and percentage of live spermatozoa.  Research was carried out to evaluate the effects of separation medium, addition of coffee extract before sexing of X and Y sperm chromosome, and storage period on the quality of goat fresh semen.  This experiment was performed according to completely randomized design in factorial pattern (2 x 2 x 6). The first factor was the separation medium (A1: 10% and A2: 30%), the second factor was the coffee extract addition (B1: 0 mM and B2: 3 mM), and the third factor was the period of storage(D1: 0 hour, D2: 2 hours, D3: 4 hours, D4: 6 hours, D5: 8 hours and D6: 10 hours). The result showed that the motility of spermatozoa Y in 30% separation medium was higher (P<0.01) than that of spermatozoa X in 10% separation medium and it was higher (P<0.05) with addition of coffee extract compared with no coffee extract addition.  Viability of spermatozoa Y was higher (P<0.05) compared with spermatozoa X and addition of coffee extract not significantly different (P>0.05) compared with no coffee extract addition. The motility and viability of spermatozoa decreased during 10 hours storage. It was concluded that the motility and viability of spermatozoa Y was higher than spermatozoa X. Coffee extract can prevent a decrease of spermatozoa motility during storage. The motility of spermatozoa and the percentage of live spermatozoa decreased during storage.